When is a trustee's decision momentous and is momentousness sufficient?. Issue 8 (11th August 2020) - Alexander, Stephen; Hooper, Katie
Abstract: How should a trustee judge whether or not a decision is momentous, justifying an application for a blessing on Public Trustee v Cooper principles and what will the Court's approach be if the decision put before it is, in fact, routine in nature? If a decision may be properly characterised as momentous, when will the court nonetheless refuse to bless it and to how much scrutiny will the decision be subject in this regard? These are questions with which the Royal Court of Jersey has had to grapple in two recent decisions, and those decisions provide useful lessons to trustees.